Chromatographic behavior of small organic compounds in low‐temperature high‐performance liquid chromatography using liquid carbon dioxide as the mobile phase. Issue 14 (29th May 2015) - Motono, Tomohiro; Nagai, Takashi; Kitagawa, Shinya; Ohtani, Hajime
<x xml:space="preserve">Abstract</x> Low‐temperature high‐performance liquid chromatography, in which a loop injector, column, and detection cell were refrigerated at –35ºC, using liquid carbon dioxide as the mobile phase was developed. Small organic compounds (polyaromatic hydrocarbons, alkylbenzenes, and quinones) were separated by low‐temperature high‐performance liquid chromatography at temperatures from –35 to –5ºC. The combination of liquid carbon dioxide mobile phase with an octadecyl‐silica (C18) column provided reversed phase mode separation, and a bare silica‐gel column resulted in normal phase mode separation. In both the cases, nonlinear behavior at approximately –15ºC was found in the relationship between the temperature and the retention factors of the analytes (van't Hoff plots). In contrast to general trends in high‐performance liquid chromatography, the decrease in temperature enhanced the separation efficiency of both the columns.